The Impact of Societal Vulnerability and Violent Values on Self-Control in a Belgium Sample of Youth: A Gender Comparison. (February 2013) - Gavray, Claire; Vettenburg, Nicole; Pauwels, Lieven; Brondeel, Ruben
The present study contributes to the study of self-control among adolescents by testing how self-control is affected by societal vulnerability and violent values and by investigating how (in)variant this relationship is for boys and girls. The Belgian International Self-Report Delinquency Study (ISRD-2) data were used to assess to what extent positive attitudes toward violence can be seen as mediators in the relationship between societal vulnerability and self-control. The findings suggest that violent values mediate the relationship between societal vulnerability and self-control. Despite results indicating higher self-control among females, when conducting the analyses separately by gender, we found that the relationship between societal vulnerability and self-control was very similar for boys and girls. It is concluded that societally vulnerable boys and girls are equally affected by the intermediate mechanism of violent values.